African Elephant Specialist Group report / Rapport du Groupe des Specialiste des Éléphants d'Afrique - Dublin, Holly (Pachyderm, 2005)
This text is a review of the ongoing work of the Secretariat and AfESG as a whole: reviews data collection towards AESR 2006; notes the ongoing development of subregional and national conservation and management stategies in Central, Southern, West and East Africa; discusses human-elephant conflict training, management and cooperative ventures with IUCN; the updating of AfESG's website, and the initiation of the Local Overpopulations Task Force.